Serum extracellular vesicle MicroRNAs as candidate biomarkers for acute rejection in patients subjected to liver transplant - Wang, Wenjing; Li, Wen; Cao, Li; Wang, Bo; Liu, Chang; Qin, Yannan; Guo, Bo; Huang, Chen (Frontiers in Genetics, 2022)
Acute rejection (AR) is a common and grave complication of liver transplantation (LT). The diagnosis of AR is challenging because it has nonspecific clinical features and requires invasive procedures. Since extracellular vesicles (EVs) are promising candidates as indicators for diagnosis of various diseases, this study aimed to identify serum EV microRNAs (miRNAs) as potential biomarkers for AR in patients subjected to LT. We collected clinical information and serum samples from the liver transplant recipients with and without AR (non-AR). EVs from the serum were isolated via ultracentrifugation and identified using transmission electron microscopy, nanoparticle tracking analysis, and western blotting. EV RNA was extracted and sequenced on an Illumina HiSeq 2500/2000 platform to identify differentially expressed miRNAs between the groups. Gene Ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) enrichment analyses were performed on the target gene candidates of the differentially expressed miRNAs to test their functions in biological systems. Then, we validated 12 differentially expressed miRNAs by quantitative real-time PCR. The results demonstrated that 614 EV miRNAs were significantly altered (387 upregulated and 227 downregulated) between non-AR and AR patients. GO enrichment analysis revealed that these target genes were related to cellular processes, single-organism processes, biological regulation, metabolic processes, cells, cell parts, protein-binding processes, nucleoid binding, and catalytic activity. Furthermore, KEGG pathway analysis demonstrated that the target genes of the differentially expressed miRNAs were primarily involved in ubiquitin-mediated proteolysis, lysosomes, and protein processing in the endoplasmic reticulum. miR-223 and let-7e-5p in AR patients were significantly up-regulated compared to those in non-AR patients, whereas miR-199a-3p was significantly down-regulated, which was consistent with sequencing results. The expression of serum EV miRNAs (up-regulated: miR-223 and let-7e-5p and miR-486-3p; down regulated: miR-199a-3p, miR-148a-3p and miR-152-3p) in AR patients was significantly different from that in non-AR patients, and these miRNAs can serve as promising diagnostic biomarkers for AR in patients subjected to liver transplant.